1960
DOI: 10.1103/physrev.120.2033
|View full text |Cite
|
Sign up to set email alerts
|

Momentum Distributions of Photons from Positrons Annihilating in Alkali Halides

Abstract: The angular correlation of photons from the two-gamma decay of positrons in all sodium halides and all alkali chlorides has been measured. The data yields the momentum distribution of the two gamma rays which is also the momentum distribution of the annihilating electron-positron pairs. It is seen that the positive ion has very little influence on the momentum distribution in comparison with the negative ion. These distributions in momentum are compared with the distributions calculated from various models of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1967
1967
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…In earlier work (Ferrell 1956) the positron wavefunction was represented by a 6 function, at the ionic radius. Later assuming the positron to be bound to an ion, Stewart and Pope (1960) represented the radial part of the positron wavefunction by an analytical function of the form re-"' with an adjustable parameter (x). The Wigner-Seitz (WS) approximation has been used to estimate the wavefunction and energy of the lowest single-particle positron state in perfect metals first by Berko and Plaskett (1958) and later by many authors (Rose and De Benedetti 1965, Terre11 et n E 1965, Chaung and Hogg 1967.…”
Section: Calculational Methodsmentioning
confidence: 99%
“…In earlier work (Ferrell 1956) the positron wavefunction was represented by a 6 function, at the ionic radius. Later assuming the positron to be bound to an ion, Stewart and Pope (1960) represented the radial part of the positron wavefunction by an analytical function of the form re-"' with an adjustable parameter (x). The Wigner-Seitz (WS) approximation has been used to estimate the wavefunction and energy of the lowest single-particle positron state in perfect metals first by Berko and Plaskett (1958) and later by many authors (Rose and De Benedetti 1965, Terre11 et n E 1965, Chaung and Hogg 1967.…”
Section: Calculational Methodsmentioning
confidence: 99%
“…7 As has been extensively discussed in the case of electrons 6 and briefly made plausible for Ps, 1 "" 4 it is reasonable to assume that the c. m. of the Ps atom is mostly confined to a bubble represented by a sharp spherical (for s states) potential well. Within the well the potential is taken as zero (as in a vacuum) and outside the well the potential is taken as V 0 which, for example, can be estimated by a Wigner-Seitz model calculation for the lowest energy state of a Ps atom in helium at its normal density.…”
Section: General Modelmentioning
confidence: 99%
“…Experiments on the alkali halides have indicated that, the 2-photon angular correlation are almost independent of the positive ions [6] that is, they are only dependent on the negative ions. Theoretically then this is interpreted to mean that in an ionic crystal the positron wave function is concentrated about the negative ions and therefore The experimental angular correlation curves are shown in Fig.…”
Section: S Y Chuang and B G Hwgmentioning
confidence: 99%